2008
DOI: 10.1103/physrevlett.101.116102
|View full text |Cite|
|
Sign up to set email alerts
|

Interplay between External Strain and Oxygen Vacancies on a RutileTiO2(110)Surface

Abstract: Comprehensive first-principle calculations on strained rutile TiO2(110) indicate that the formation energy of different types of oxygen vacancies depends on the external strain. For the unstrained state, the energetically favorable oxygen vacancy (EFOV) appears on the bridging site of the first layer; when 3% tensile strain along [11[over ]0] is applied, EFOV moves to the in-plane site, while 2% compressive strain along either [001] or [11[over ]0] shifts EFOV to the subbridging site. We therefore suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 34 publications
0
35
1
Order By: Relevance
“…The valence band maximum lies below E F and conduction band minimum lies above E F proton mobility in hydrated conditions, where a BaZr 0:9 Y 0:1 O 3 shows larger lattice parameter due to the hydrostatic pressure induced by the syntheses route [36]. The discrepancies may be due to several differences in the system and the environmental conditions, such as the hydrated conditions, under which the experiment has been performed, which means that water is present and hydroxyls can form, do not resemble our simulated conditions [37,38]. However, Ottochan et al analysed proton conduction in Yttrium-doped BaZrO 3 under biaxial compressive conditions through the use of reactive molecular dynamics simulations.…”
Section: Resultsmentioning
confidence: 72%
“…The valence band maximum lies below E F and conduction band minimum lies above E F proton mobility in hydrated conditions, where a BaZr 0:9 Y 0:1 O 3 shows larger lattice parameter due to the hydrostatic pressure induced by the syntheses route [36]. The discrepancies may be due to several differences in the system and the environmental conditions, such as the hydrated conditions, under which the experiment has been performed, which means that water is present and hydroxyls can form, do not resemble our simulated conditions [37,38]. However, Ottochan et al analysed proton conduction in Yttrium-doped BaZrO 3 under biaxial compressive conditions through the use of reactive molecular dynamics simulations.…”
Section: Resultsmentioning
confidence: 72%
“…24,27 The evolution of strain in (110) surface induced by oxygen vacancies is in agreement with the reported prediction of first principle calculations. 40 In very recent work, the same group has also shown that this kind of strain engineering can be used to tailor the elastic properties and reactivity of the surfaces. 21 For the evidence of loss of stoichiometry in irradiated film, the loss of oxygen is confirmed by the cross sectional line scan of energy dispersive x-ray (EDX) analysis as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, both the adsorption process and the equilibrium vacancy concentrations contribute to the TM oxide reactivity. While the underlying strain effects were shown to alter the stable oxygen-vacancy configurations in some oxide systems, [10][11][12] systematic studies to clarify the competing microscopic mechanisms and the magnitude of these effects have not been carried out.…”
Section: Introductionmentioning
confidence: 99%